A conservation planning approach to mitigate the impacts of leakage from protected area networks. Issue 3 (11th December 2014) - Bode, Michael; Tulloch, Ayesha I. T.; Mills, Morena; Venter, Oscar; W. Ando, Amy
Abstract: Protected area networks are designed to restrict anthropogenic pressures in areas of high biodiversity. Resource users respond by seeking to replace some or all of the lost resources from locations elsewhere in the landscape. Protected area networks thereby perturb the pattern of human pressures by displacing extractive effort from within protected areas into the broader landscape, a process known as leakage. The negative effects of leakage on conservation outcomes have been empirically documented and modeled using homogeneous descriptions of conservation landscapes. Human resource use and biodiversity vary greatly in space, however, and a theory of leakage must describe how this heterogeneity affects the magnitude, pattern, and biodiversity impacts of leakage. We combined models of household utility, adaptive human foraging, and biodiversity conservation to provide a bioeconomic model of leakage that accounts for spatial heterogeneity. Leakage had strong and divergent impacts on the performance of protected area networks, undermining biodiversity benefits but mitigating the negative impacts on local resource users. When leakage was present, our model showed that poorly designed protected area networks resulted in a substantial net loss of biodiversity. However, the effects of leakage can be mitigated if they are incorporated ex‐ante into the conservation planning process. If protected areas are coupled with nonreserve policy instruments such as market subsidies, our model shows that the trade‐offs between biodiversity and human well‐being can be further and more directly reduced. Abstract : Una Estrategia de Planificación de la Conservación para Mitigar los Impactos de Fugas en Redes de Áreas Protegidas Resumen: Las redes de áreas protegidas están diseñadas para restringir las presiones antropogénicas en áreas de alta biodiversidad. Los usuarios de los recursos responden al buscar reemplazar algunos o todos los recursos perdidos en otras localidades del terreno. Por esto las redes de áreas protegidas perturban el patrón de presiones humanas al desplazar el esfuerzo extractivo dentro de las áreas protegidas hacia un terreno más amplio, un proceso conocido como fuga. Los efectos negativos de la fuga sobre los resultados de conservación han sido documentados empíricamente y modelados usando descripciones homogéneas de terrenos de conservación. El uso de recursos por los humanos y la biodiversidad varían ampliamente en el espacio, sin embargo, y una teoría de fuga debe describir cómo esta heterogeneidad afecta a la magnitud, el patrón y a los impactos de la fuga sobre la biodiversidad. Combinamos modelos de utilidad del hogar, búsqueda adaptativa de alimento por humanos y conservación de la biodiversidad para proporcionar un modelo bio‐económico de fuga que represente la heterogeneidad espacial. La fuga tuvo impactos fuertes y divergentes sobre el desempeño de las redes de áreas protegidas, debilitando a los beneficios de la biodiversidad pero mitigando los impactos negativos sobre los usuarios locales de recursos. Cuando la fuga estuvo presente, nuestros modelos mostraron que las redes de áreas protegidas diseñadas pobremente resultaron en una pérdida neta sustancial de biodiversidad. Sin embargo, los efectos de la fuga pueden mitigarse si se incorporan ex‐ante al proceso de planificación de la conservación. Si las áreas protegidas se emparejan con instrumentos de política ajena a las reservas, como los subsidios de mercado, nuestro modelo muestra que las compensaciones entre la biodiversidad y el bienestar humano puede reducirse más y de manera más directa.